2019
DOI: 10.1002/ajhb.23244
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance vector values in a Spanish healthy newborn population for nutritional assessment

Abstract: Introduction Vector bioimpedance analysis (BIVA) can be very useful for the evaluation of body composition, hydration, and nutritional status in infants and newborns. The objective of this study was to determine the impedance vector distribution for a group of healthy newborn Spanish children. Methods This was a cross‐sectional, descriptive study conducted with 154 healthy, Spanish newborns (gestational age: 37‐41 weeks) aged 24 to 72 hours (79 males, 75 females). Weight, height, and cephalic‐circumference wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…These include the works of Piccoli, A. and his team in normal adults or with conditions associated with or without edema [41e43]; as well as in normal infants and children [36,37]. We also included other studies looking at groups of healthy infants [44], and non-European children that are either healthy, with severe wasting or with edematous SAM [19,32,45,46]. Our data aligns well with these reported findings.…”
Section: Betweensupporting
confidence: 84%
See 1 more Smart Citation
“…These include the works of Piccoli, A. and his team in normal adults or with conditions associated with or without edema [41e43]; as well as in normal infants and children [36,37]. We also included other studies looking at groups of healthy infants [44], and non-European children that are either healthy, with severe wasting or with edematous SAM [19,32,45,46]. Our data aligns well with these reported findings.…”
Section: Betweensupporting
confidence: 84%
“…Perhaps, our younger population with small body size and severe conditions compound the above listed factors that influence BI measures. For example, high variance of PA and BI variables has been discussed in ill malnourished adults with cancer [58], and in healthy infants [44,57]. Also, as reviewed in Rinaldi, S. et al [59], the use of PA has not been validated for clinical use in diseased adults with no established guidelines or cut-offs for malnutrition screening or assessment.…”
Section: Discussionmentioning
confidence: 99%
“…However, using the same technique and repeated measurements to follow up the patients status seems to be worth doing. Over the last decade, various methods based on bioimpedance techniques have been used to assess the nutritional status in patients with CKD, inflammatory bowel disease, neurological diseases or general population from new-borns to elderly [13][14][15][16][17]. However, data regarding the usage of bioelectrical impedance in nephrotic syndrome is limited.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, distances between electrodes ranging from 2 to 6 cm have been suggested for the pediatric population, although a consensus has not been reached. In some published studies, the distance used between electrodes is not reported, which complicates comparisons of published results 7–11 . The current study did not aim to define the ideal locations of electrodes but instead sought to prove that electrode positioning affects R results.…”
Section: Discussionmentioning
confidence: 99%
“…In some published studies, the distance used between electrodes is not reported, which complicates comparisons of published results. [7][8][9][10][11] The current study did not aim to define the ideal locations of electrodes but instead sought to prove that electrode positioning affects R results. To obtain reliable results, allowing comparisons between different studies, the technique must be standardized, especially in preterm infants.…”
Section: Discussionmentioning
confidence: 99%